THE LIVING QUR’AN: MAKNA MUJAHADAH DI PONDOK PESANTREN ISC ASWAJA LINTANG SONGO PIYUNGAN BANTUL YOGYAKARTA - Dwi Khalimas Segar; Fajar Wati, Erika Aulia (IAIN Madura, 2022)
Al-Quran is a Muslim holy book that serves as a way of life as well as an authoritative source of Sharia in social life, with the meaning of the Quran verses continuing to change. The theoretical and practical potential of developmental relationship between the meaning of each Qur’anic verse reading is worth exploring. In terms of theory, the Quran would be subjected to an understanding reconstruction. It will continue to be developed with diverse information and sharing techniques. The practical study of the Quran, on the other hand, is concerned with how the Qur’an passages might be comprehended and applied in daily life. In this study, the reality of the community’s interaction with the Qur’an was directly assessed, particularly in Pondok Pesantren ISC Aswaja Lintang Songo. The mujahadah community use Quranic verses as incantation which is believed having magical and mystical energy. For the people, Qur’an recitation during mujahadah contains values which cannot be stated but can only be felt by those who implement it. As a result, the verses of the Qur'an live in society based on their perception and appreciation.